PENGARUH PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN EDMODO TERHADAP HASIL BELAJAR SISWA KELAS VIII MTS MAHAD PANGKAJENE : PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN EDMODO TERHADAP HASIL BELAJAR SISWA KELAS VIII MTS MAHAD PANGKAJENE - M. Daming, Hamdi; Yanti, Nur Eva (CV. LAJAGOE PUSTAKA, 2023)
ABSTRACT The sample of this study is class VIII, totaling 30 students. The data collection techniques used in this study are documentation and test techniques, for data analysis techniques in this study using the Mean formula. Based on the results of the study, according to hypothesis testing through data analysis, the results of the control group (Y) were lower than the test results of the experimental group (X), namely Y = 66.33 < X = 88.26 The difference in the results of these values ​​proves that the hypothesis The work which states that there is an effect of using Edmodo Media on the learning outcomes of students of Islamic Cultural History class VIII Mts Mahad Pangkajene